Morphological description and DNA barcoding of Diamesa achipseensis sp. nov. (Diptera: Chironomidae: Diamesinae) from Southwestern Caucasus - Makarchenko, Eugenyi A.; Semenchenko, Alexander A.; Palatov, Dmitry M. (Zootaxa, 2024)
Illustrated description of adult male, as well as DNA barcoding, of Diamesa achipseensis sp. nov. in comparison with close related species D. caucasica Kownacki et Kownacka from Southwestern Caucasus are provided. Interspecific distances between D. achipseensis sp. nov. and D. caucasica are extremely low (0.64% in average) despite the identified morphological differences. High similarity of these species is new example of genetically indistinguishable of some species of the genus Diamesa Meigen.